Operational suitability assessment of information resources for a geospatial environmental database unity - Yulia Kroumova; Tanya Trenkova; Stoyan Nedkov; Aleksandra Ravnachka (GeoStudies)
In the contemporary digital world, data is a pivotal capital considered an economic factor for generating digital products and services. The rapid growth in data volume and their heterogeneity requires optimization of the data management in order to extract higher added value from them. In the context of this issue, one of the goals of the National Scientific Program “Environmental Protection and Risk Reduction from Adverse Events and Natural Disasters” is the creation of a unified geo-informational environment integrating the data from the work packages. To realize this goal, the present study examines certain aspects of data quality related to their usability. By reviewing basic standards for geospatial data, the metadata paradigm, and previous experience in data quality assessment, a theoretical framework with the main stages of a methodological approach evaluating the suitability of primary data sources for building a unified geoinformation database has been developed. The research results reflect the application of developed criteria systems (detailed and generalized) in analyzing the quality and the study of the suitability degree of selected information resources for one of the Program’s working packages. The results of extensive surveys from work program packages have been generalized. Selected primary data sources have been catalogued, and a multicriteria methodological approach has been developed to assess their quality in terms of their suitability for the unity of the database.